PROFIL ALBUMINURIA DAN KADAR sVCAM-1 PADA PENDERITA DIABETEES MELITUS TIPE 2 - C, Wibisono; A, Fajar; A, Tjokroprawiro; A, Soetjahjo; A, Pranoto; S, Adi; S, Murtiwi (journal of internal medicine; Vol. 13, No. 1 Januari 2012, 2014)
Vascular complications develop progressively from 5 ? 40 years after the onset of diabetes, although they may appear earlier in type 2 diabetes when associated with a periode of undiagnosed diabetes and impaired glucose tolerance. Endothelial dysfunction is the proposed site of both micro vascular and macro vascular complications in diabetes. Endothelial dysfunction has been documented in both type1 and type 2 diabetes and is present in the insulin resistance syndrome and in pre diabetes. There were will likely be a subsequent increased burden of vascular complications of diabetes, including diabetic nephropathy (DN). It is predicted that 25% of newly diagnosed patient with type 2 diabetes will develop early stage DN within the next 10 years. Advanced Glycation End Products (AGEs), which accumulate in diabetic vasculature, result in enhanced expression of endothelial cell-associated Vascular Cell Adhesion Molecule-1 (VCAM-1) as well release of a soluble form of VCAM-1 (sVCAM-1) into culture supernatants. We hypothesized that sVCAM-1 in diabetic plasma might reect early vascular perturbation in diabetic vasculopathy. The aims of this study is to know the prol of sVCAM-1 and albuminuria in type 2 diabetes. A cross sectional study to measure sVCAM-1and albuminuria. Descriptive statistical analysis used to know the prol of sVCAM-1 and albuminuria. Of the 69 diabetic subjects (31 males, 38 Females) with mean age of 57.4 ± 4.8 years, normoalbuminuria 39 subjects, microalbuminuria 23 and macroalbuminuria 7 patients, and sVCAM-1 was 0.614 ± 0.177. The levels of sVCAM-1 plasma is increased along with stage of albuminuria. There was an increase of sVCAM-1 level along with stage of albuminuria.
Keywords: Diabetes nephropathy, diabetes, VCAM-1, albuminuria, hyperglycemia